2020
DOI: 10.1128/aac.01283-20
|View full text |Cite
|
Sign up to set email alerts
|

(p)ppGpp and Its Role in Bacterial Persistence: New Challenges

Abstract: Antibiotic failure is not only due to the development of resistance by pathogens, but it can also often be explained by persistence and tolerance. Persistence and tolerance can be included in the “persistent phenotype”, with high relevance for clinics. Two of the most important molecular mechanisms involved in tolerance and persistence are toxin-antitoxin (TA) modules and signaling via guanosine pentaphosphate/tetraphosphate (p)ppGpp, also known as “magic spot”). (p)ppGpp is a very important stress alarmone wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 106 publications
1
88
0
Order By: Relevance
“…The alarmone molecule guanosine pentaphosphate/tetraphosphate, (p)ppGpp, has been shown to control the expression of TA systems and play important roles in persister formation as well as the bacterial response to environmental stresses, such as oxidative stress, starvation, etc. [ 59 , 60 ]. Meanwhile, it has been demonstrated that (p)ppGpp controls global gene expression and contributes to bacterial virulence in various infection models [ 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The alarmone molecule guanosine pentaphosphate/tetraphosphate, (p)ppGpp, has been shown to control the expression of TA systems and play important roles in persister formation as well as the bacterial response to environmental stresses, such as oxidative stress, starvation, etc. [ 59 , 60 ]. Meanwhile, it has been demonstrated that (p)ppGpp controls global gene expression and contributes to bacterial virulence in various infection models [ 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies are ongoing to find drugs that would inhibit Rel proteins (11, 13), as such drugs are expected to increase susceptibility to other clinically available antibiotics. Our results indicate that Rel inhibitors, should they become available, might actually increase tolerance when administered in combination with amikacin to treat Mab infections, and may have no effect with clarithromycin and cefoxitin.…”
Section: Resultsmentioning
confidence: 99%
“…1). In many species, the stringent response upregulates stress response genes such as heat shock proteins, hibernation factors, and stress-specific transcription factors (3, 41, 42) and promotes survival in stress (13) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, reconstruction of this mutant strain demonstrated that deletion of the 10 TA systems did not affect susceptibility to ofloxacin or ampicillin [106]. These contradictory findings have given rise to considerable debate [78,[107][108][109], and the relevance of TA systems to bacterial persistence remains unclear.…”
Section: Role Of Type II Ta Modules In Biofilm Formation and Bacteriamentioning
confidence: 98%